Blood Q Creatinine Based on Sex and Age in Healthy Indonesian Geriatrics - Marpaung, Ferdy Royland; Santoso, Djoko; Cavalier, Etienne; Aryati, Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Median blood creatinine (Qcr) is necessary for an accurate evaluation of geriatric renal function. Nonetheless, there is a significant void in existing literature concerning creatinine reference data unique to the elderly. To improve diagnostic precision and clinical decision making in this susceptible group, this study developed a corresponding Q model for serum creatinine in geriatric patients stratified by age and sex. To determine the Qcr serum and reference range creatinine concentrations, 913 healthy elderly patients (452 males and 461 females) undergoing routine examinations at clinical laboratories were studied. Creatinine concentration reference intervals were divided into 3 age groups, namely: 60-69 years, 70-79 years, and >80 years. The median and percentiles p2.5 (lower reference limit/LRL) and p97.5 (upper reference limit/URL) were determined by the study. The study determined the Qcr serum creatinine and reference values for the elderly, stratified by age and sex. There were no significant differences observed in creatinine level across the age group, either in males or females. Males exhibited higher creatinine compared to females (p <0.05). These recently developed, age and sex stratified Qcr values are an invaluable tool for clinical laboratories, enabling more precise, tailored care for elderly patients with renal issues and enabling clinicians to more accurately assess geriatric renal function.